Fracture toughness of three-dimensional printed and milled denture bases - Walaa A. Babeer (PLoS ONE, 2025)
Denture base fractures are a common issue, particularly in overdentures, necessitating high fracture toughness in denture base polymers to withstand oral mechanical loads. Despite the importance of fracture resistance, current denture base materials often fall short of meeting the required standards. The literature shows conflicting results regarding the fracture toughness of three-dimensional (3D)-printed materials compared to conventional and milled options. This study aimed to address this gap by evaluating the fracture toughness of commercially available digital denture base resins, including two CAD/CAM-milled and two 3D-printed materials. Using a three-point bending test on notched beams according to ISO 20795–1:2013 standards, the study compared the fracture toughness of FormLabs denture base LP, NextDent Denture 3D, AvaDent, and XANTECH PMMA. Results revealed that NextDent exhibited the highest fracture toughness, suggesting better crack propagation resistance. Printed acrylic (NextDent) and prepolymerized polymethyl methacrylate (AvaDent and XANTECH) demonstrated superior fracture toughness compared to Formlabs photopolymerized diurethane methacrylate. However, none of the tested materials met the ISO’s highest impact resistance requirements. These findings highlight the variability in fracture toughness among different manufacturing techniques and compositions, emphasizing the need for further research to develop denture base materials with enhanced impact resistance. This study provides valuable insights for clinicians in material selection for denture fabrication and underscores the importance of continued innovation in dental materials to improve the longevity and performance of prosthetic devices.